Phonological Aspects of English Language Proficiency at the Junior High School Level - Ahmad Syafiq; Bastian Sugandi (Universitas Muhammadiyah Lampung, 2024)
This study aims to describe the phonological aspects of English pronunciation mastery among eighth-grade students of SMP Muhammadiyah Pringsewu. The research focuses on students ability to pronounce English sounds, including vowels and consonants, word stress, and sentence intonation, as well as identifying dominant phonological errors and the factors influencing them. A qualitative descriptive approach was employed in this study. The research subjects consisted of 20 eighth-grade students. Data were collected through classroom observation, a pronunciation test, and interviews. The findings reveal that students are generally able to pronounce basic English sounds, particularly those similar to Indonesian phonological features. However, difficulties were still observed in pronouncing specific English sounds such as the interdental sounds /?/ and //, the fricative /?/, distinctions between long and short vowels, as well as in applying appropriate word stress and intonation. The main phonological errors include sound substitution, incorrect stress placement, and flat intonation patterns. These difficulties are influenced by first-language interference, limited pronunciation practice, and minimal exposure to authentic English pronunciation. The study concludes that although students have acquired a basic level of phonological competence, their mastery remains moderate and needs further development. Therefore, more structured and continuous pronunciation practice is vital to improve students phonological awareness and speaking proficiency.